INFLUENCE OF TEMPERATURE AND DIFFERENT METHODS OF THERMAL PROCESSING TO COLOR CHANGES AND SENSORY CHARACTERISTICS OF PORK MEAT - Radoslav Grujić; Dragan Vujadinović; Vladimir Tomović (Journal of Engineering & Processing Management, 2013)
Meat is very important ingredients in the human diet, so it is a source of easily digestible, biological and energy valuable components. Therefore, this paper investigate the influence of temperature in the temperature range from 51℃ to 100 ℃ and different methods of thermal processing, thermal treatment by cooking and roasting, to change the color and sensory characteristics of pork meat. As parameters to change the color on the surface of the treated samples, were measured L* a* and b* value in CIE L*a*b* system. Sensory properties were evaluated juiciness, tenderness, amount of connective tissue and aroma. This research showed that thermal treatment of roasting has a more intense effect on the change of parameters L* a* and b*, while cooking thermal treatment more intensive affects the change of sensory qualities.
Keywords: pork meat; meat color; thermal treatment of meat; sensory properties of meat